Tourists’ Views on Sustainable Heritage Management in Porto, Portugal: Balancing Heritage Preservation and Tourism - Makhabbat Ramazanova; Fátima Matos Silva; Isabel Vaz de Freitas (Heritage)
This research explores the perceptions of tourists regarding the state and sustainable management of tangible cultural heritage in the city of Porto (Portugal), the destination recognised for its historical and cultural heritage. Porto attracts a growing number of tourists due to its rich heritage, encompassing cultural, architectural, and scenic elements. This rising demand necessitates sustainable management practices to protect the city’s heritage and ensure long-term sustainability. With the increase in tourism and the need to preserve cultural and environmental resources, sustainable management becomes essential to balance economic development and heritage conservation. The study’s main objective is to analyse tourists’ perspectives on the sustainable management of the cultural heritage of the city of Porto. It focuses on analysing current tourism management practices and calls for new strategies to promote sustainability. Structured questionnaires were distributed to a random sample of tourists in strategic locations between January and April 2023, obtaining quantitative data. The sample consists of 264 respondents. The results revealed four main factors, showing that most respondents show a high level of awareness and appreciation of sustainability and its relevance for heritage conservation. Regarding tourism, the majority agree that it contributes positively to the conservation and restoration of the city’s heritage.